Atlas of Genetic Diagnosis and Counseling - Chen, Harold (Springer New York : Imprint: Springer, 2017)
Dr. Harold Chen shares his almost 50 years of clinical genetics practice in this new edition of a comprehensive pictorial atlas, featuring almost 290 genetic disorders, malformations, and malformation syndromes. The author provides a detailed outline for each disorder, describing its genetics, basic defects, clinical features, diagnostic tests, and counseling issues, including recurrence risk, prenatal diagnosis, and management. Numerous color photographs of prenatal ultrasounds, imagings, cytogenetics, and postmortem findings illustrate the clinical features of patients at different ages, patients with varying degrees of severity, and the optimal diagnostic strategies. The disorders cited are supplemented by case histories and diagnostic confirmation by cytogenetics, biochemical, and molecular techniques, when available. Since the publication of the previous edition in 2012, the atlas has been widely accepted and used in light of rapid progress in genetic and gnomic information. In this new edition, additional genetic disorders are added, as well as extensive updates to the previous disorders with new illustrations, supplemented by case and family history, clinical features, and laboratory data, especially molecular confirmation if available. The atlas is written in outline format for ease of use. Atlas of Genetic Diagnosis and Counseling, Third Edition is of great value to medical geneticists, genetic counselors, pediatricians, neonatologists, developmental pediatricians, perinatologists, obstetricians, neurologists, pathologists, and any physicians and health care professionals caring for handicapped children such as craniofacial surgeons, plastic surgeons, otolaryngologists, and orthopedists. It is the definitive volume for helping all physicians to understand and recognize genetic diseases and malformation syndrom es and better evaluate, counsel, and manage affected patients.- Resumé vydavatel